Understanding employee motivation to innovate: Evidence from front line employees in United States - Fernandez, Sergio; Pitts, David W. (2011)
In a period of ongoing public sector reform in the United States (US), federal government agencies have been pushed to find new ways of performing their public functions more effectively and efficiently. Frontline public sector employees are a particularly vital source of innovations in organisational function and form. This study seeks to identify factors that motivate front line employees in the US federal bureaucracy to engage in innovative behaviour. The empirical analysis is based on data from the 2006 Federal Human Capital Survey. The results show that a constellation of factors encourage bottom-up innovation, including the expectancy of innovation being rewarded, employee training and development, employee empowerment and involvement in decision-making, and high-exchange dyadic relationships and supervisors. - Reproduced.
Keywords: Employees; Motivation